Diagnóstico e planejamento em cirurgia parendodôntica: utilização da tomografia cone beam - Lima, Regina Karla Pontes [UNESP]; Faria Júnior, Norberto Batista de [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Tanomaru Filho, Mário [UNESP] (My University, 2010)
The ability to tridimensionally evaluate pathological and anatomical areas, in apical surgery planning, presents a number of advantages. Cone beam computed tomography (CBCT) was developed for dental applications. This paper aims to present a literature review on CBCT, highlighting its advantages over both conventional computed tomography (CT) and radiography. Moreover, its clinical applications in apical surgery are discussed. LITERATURE REVIEW AND CONCLUSION: Unlikely CT, CBCT captures a volume of data in a single 360º rotation, providing benefits such as higher accuracy, better resolution, reduced scanning time and reduced radiation dose. In the maxillofacial region, CBCT has been mainly used in the assessment of dento-alveolar pathology and oral traumatology. CBCT provides a better diagnosis and quantitative information on periodontal bone levels than conventional radiography. It has also been used for patients requiring surgical facial reconstruction, orthognathic surgery, dental implants, and more complex tooth extractions. Besides that, it seems to be a significant tool in modern endodontic practice, presenting useful applications in apical surgery.

A capacidade de avaliar áreas patológicas e anatômicas em três dimensões no planejamento de cirurgia parendodôntica apresenta uma série de vantagens. A tomografia computadorizada cone beam (TCCB) foi desenvolvida para aplicações odontológicas. Os objetivos deste artigo são realizar um levantamento bibliográfico sobre a TCCB, destacando suas vantagens em relação à tomografia computadorizada convencional (TC) e à radiografia convencional, e discutir suas aplicações clínicas na cirurgia parendodôntica. REVISÃO DE LITERATURA E CONCLUSÃO: Diferentemente da TC, a TCCB captura um volume de dados em uma rotação única de 360º, oferecendo vantagens como maior precisão, melhor resolução, redução do tempo de digitalização e diminuição da dose de radiação. Na região maxilofacial, a TCCB é mais usada na avaliação de patologia dentoalveolar e na traumatologia bucal. A TCCB favorece o diagnóstico e a análise quantitativa do nível ósseo alveolar e tem sido utilizada em pacientes que necessitam de cirurgia de reconstrução facial, cirurgia ortognática, implantes dentários, exodontias mais complexas, além de ser uma ferramenta valiosa na prática endodôntica moderna, com importantes aplicações na cirurgia parendodôntica.
Diagnosis and planning in apical surgery: use of cone-beam tomography
Keywords: Oral surgery; Three-dimensional imaging; Cone beam computed tomography; Cirurgia bucal; Imagem tridimensional; Tomografia computadorizada de feixe cônico